Feasibility and Accuracy of Thoracolumbar Minimally Invasive Pedicle Screw Placement With Augmented Reality Navigation Technology. Issue 14 (15th July 2018) - Elmi-Terander, Adrian; Nachabe, Rami; Skulason, Halldor; Pedersen, Kyrre; Söderman, Michael; Racadio, John; Babic, Drazenko; Gerdhem, Paul; Edström, Erik
Abstract : Study Design: Cadaveric laboratory study. Objective: To assess the feasibility and accuracy of minimally invasive thoracolumbar pedicle screw placement using augmented reality (AR) surgical navigation. Summary of Background Data: Minimally invasive spine (MIS) surgery has increasingly become the method of choice for a wide variety of spine pathologies. Navigation technology based on AR has been shown to be feasible, accurate, and safe in open procedures. AR technology may also be used for MIS surgery. Methods: The AR surgical navigation was installed in a hybrid operating room (OR). The hybrid OR includes a surgical table, a motorized flat detector C-arm with intraoperative 2D/3D imaging capabilities, integrated optical cameras for AR navigation, and patient motion tracking using optical markers on the skin. Navigation and screw placement was without any x-ray guidance. Two neurosurgeons placed 66 Jamshidi needles (two cadavers) and 18 cannulated pedicle screws (one cadaver) in the thoracolumbar spine. Technical accuracy was evaluated by measuring the distance between the tip of the actual needle position and the corresponding planned path as well as the angles between the needle and the desired path. Time needed for navigation along the virtual planned path was measured. An independent reviewer assessed the postoperative scans for the pedicle screws' clinical accuracy. Results: Navigation time per insertion was 90 ± 53 seconds with an accuracy of 2.2 ± 1.3 mm. Accuracy was not dependent on operator. There was no correlation between navigation time and accuracy. The mean error angle between the Jamshidi needles and planned paths was 0.9° ± 0.8°. No screw was misplaced outside the pedicle. Two screws breached 2 to 4 mm yielding an overall accuracy of 89% (16/18). Conclusion: MIS screw placement directed by AR with intraoperative 3D imaging in a hybrid OR is accurate and efficient, without any fluoroscopy or x-ray imaging during the procedure. Level of Evidence: N/A